Neuropathy and the automatic analysis of electromyographic signals from vibration exposed workers. - Alaranta, Hannu; Seppäläinen, A. M. (Scandinavian Journal of Work, Environment & Health, 1977)
An automatic analysis of the electromyographic activity of the extensor digitorum communis, first dorsal interosseus and opponens pollicis muscles was performed, and both motor and sensory conduction velocities of the median and ulnar nerves were measured in the study of neuropathic changes that occur in traumatic vasospastic disease. Twenty-eight forest workers and 10 pneumatic-tool operators, all with a long occupational exposure to local vibration of the hands, were studied with these neurophysiological methods and general clinical and roentgenological examinations. Twenty male manual workers with a similar age distribution served as the comparison group. The most sensitive measures which separated the subjects with traumatic vasospastic disease from the nonexposed workers were the conduction velocity of the slower motor fibers of the ulnar nerve, the distal sensory conduction velocity and the motor distal latency of the median nerve. The duration and rise time of the averaged muscular potentials of intrinsic hand muscles correlated especially with those nerve conduction velocities which were the most sensitive in exhibiting neuropathic changes.
Keywords: automatic analysis; electromyographic signal; electromyography; EMG; exposed; nerve conduction velocity; neuropathy; traumatic vasospastic disease; vibration; vibration exposed worker; worker